Faktor-Faktor Yang Mempengaruhi Integritas Laporan Keuangan - Bima Maychandra; Nelvirita Nelvirita (Universitas Negeri Padang, 2023)
The aim of this research is to examine the influence of institutional ownership, independent commissioners, audit committees and managerial ownership on the integrity of financial reports. Financial account integrity, which is measured by the market price of shares divided by the book value of shares, is the dependent variable. Meanwhile, institutional ownership is measured by the number of shares owned by the institution in the number of outstanding shares, independent commissioners are measured by the number of independent commissioners in the number of commissioners, audit committees are calculated by the number of audit committee members, and managerial ownership is measured by the number of shares owned by management in the section with number of shares distributed. The research population is companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. Purposive sampling was used to determine the research sample, and 18 companies were obtained with a total of 90 observations. Multiple linear regression analysis is used as an analysis technique. Based on the findings of this research, institutional ownership, audit committee and managerial ownership have no effect on the integrity of financial reports, but independent commissioners have a good and significant effect on the integrity of financial reports.